Cognitive Effects and Depression Associated With Taxane-Based Chemotherapy in Breast Cancer Survivors: A Meta-Analysis - Ibrahim, Eiman Y.; Domenicano, Ilaria; Nyhan, Kate; Elfil, Mohamed; Mougalian, Sarah S.; Cartmel, Brenda; Ehrlich, Barbara E. (Frontiers in Oncology, 2021)
Purpose: This meta-analysis provides a longitudinal assessment of depression and cognitive impairment induced by taxane-based chemotherapy in women with breast cancer after 6 months of treatment. We highlighted the incidence and prevalence, the cognitive pattern in neuropsychological studies, and the relationship between chemotherapy-induced cognitive impairment and different risk factors. We estimated the effect sizes on each cognitive domain and differentiated effect sizes by each method of comparison of effects (i.e. baseline data, or control groups). Methods: The databases MEDLINE and Embase were searched for publications about taxane-related cognitive changes in patients with breast cancer published from 1980 to 2019. Cross-sectional and self-reported outcomes studies were excluded except for the depression domain. Included studies were assessed for risk of bias with the Newcastle-Ottawa Scale. We estimated effect sizes for each cognitive domain and differentiated effect sizes by each method of comparison of effects. The review is reported in compliance with the PRISMA Statement; it was registered prospectively in PROSPERO as CRD42020163255. Results: Eleven studies meeting the criteria were analyzed, which resulted in a sample of 1057 breast cancer patients who received chemotherapy including 820 patient (77%) who received taxane-based chemotherapy. Attention and concentration, depression, and executive function domains had significant chemotherapy-induced impairment across all comparison types. Statistically significant improvement was found in language and verbal memory when comparing chemotherapy patients’ test scores with baseline or matched controls. Taxane-based chemotherapy had a non-significant effect on processing speed, visual memory, visuospatial, and motor function domains. Conclusions: The occurrence of chemotherapy-induced cognitive impairment 6 months or more after the course of treatment in people with breast cancer is frequent in the domains of attention, executive function, and depression. Other domains appear stable or improve with time after treatment cessation.